2022
DOI: 10.3390/nu14194010
|View full text |Cite
|
Sign up to set email alerts
|

Food Costs of Children and Adolescents Consuming Vegetarian, Vegan or Omnivore Diets: Results of the Cross-Sectional VeChi Youth Study

Abstract: The aim was to analyse the total food costs and the impact of food groups on total food costs among vegetarian, vegan and omnivore children and adolescents in Germany. Based on three-day weighed dietary records of 6–18-year-old children and adolescents of the VeChi Youth Study, the total daily food costs and food group costs (both EUR/day, EUR/1000 kcal) of a vegetarian (n = 145 records), vegan (n = 110) and omnivore (n = 135) diet were calculated. Minimum retail prices of 1000 empirically selected foods repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Arce et al (2021) found that the acceptability of some FVs is reported to have a high influence on consumption. In this sense, price as an FV consumption barrier is likely to be hiding other determinants (Livingstone et al, 2020;Hohoff et al, 2022;Young and Stewart, 2022). Of course, price is relevant in many consumption decisions; however, in some cases, it is likely to have overstated their actual effect on consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Arce et al (2021) found that the acceptability of some FVs is reported to have a high influence on consumption. In this sense, price as an FV consumption barrier is likely to be hiding other determinants (Livingstone et al, 2020;Hohoff et al, 2022;Young and Stewart, 2022). Of course, price is relevant in many consumption decisions; however, in some cases, it is likely to have overstated their actual effect on consumption.…”
Section: Discussionmentioning
confidence: 99%
“…For VN diets, it is often stated that the cost is high, and only individuals with higher economic status can afford to follow them. In contrast, studies on children, adolescents, and adults have shown that a VN diet can save on food costs [110,143,144].…”
Section: Additional Considerationsmentioning
confidence: 94%
“…Notably, more children on the OM diet were from families with a higher income status (81% vs. 62%) [109]. Moreover, financial limitations may not necessarily hinder the adoption of a plant-based dietary pattern [110].…”
Section: Studies On Vegan Vegetarian And/or Omnivorous Diets In Child...mentioning
confidence: 99%
“…11 As the affordability of such a plant-based food pattern is repeatedly debated, a further evaluation estimated the food costs of the three diet groups using Vegetarian and vegan Protein Grain and legumes (at the best in combination to enhance protein quality), soy (attention must be paid to a sufficient energy supply) 7 Long chain n-3 fatty acids Plant oils fortified or supplements with DHA from single cell/micoralgae oils, or single-oil-DHA-supplements (if applicable), optimise conversion by a ratio of linoleic acid and linolenic acid of 4:1 7 Calcium ‡ Tofu calcium-set, tempeh, sesame seeds and tahini, low-oxalate green leafy vegetables (kale, brokkoli, bok choy (pak choi), mustard greens, okra), certain beans, peas, lentils, almonds and calcium-enrichted beverages, 16 45 as well as calcium rich mineral water 24 highest intakes of vegetables, whole grain, legumes, nuts and milk alternatives in VN, less dairy intake in VG than in OM, 11 lowest estimated food costs in VG. 25 Desmond et al retail food prices. 25 It could be shown that the vegetarian food pattern was the least expensive compared with the omnivore and vegan diet pattern and food costs did not differ significantly between omnivores and vegans.…”
Section: Actual Studies On Vegetarian and Vegan Child Nutritionmentioning
confidence: 99%
“…25 Desmond et al retail food prices. 25 It could be shown that the vegetarian food pattern was the least expensive compared with the omnivore and vegan diet pattern and food costs did not differ significantly between omnivores and vegans. 25 In Poland, Desmond et al 26 cross-sectionally examined children aged 5-10 years (63 vegetarians, 52 vegans, 72 omnivores) using anthropometry, deuterium dilution, DXA, carotid ultrasound, fasting blood samples, dietary intake and accelerometery data.…”
Section: Actual Studies On Vegetarian and Vegan Child Nutritionmentioning
confidence: 99%